A SHORT GUIDE TO DEVELOPING COMMUNICATIVELY ORIENTED TEXBOOK ON SPEECH CULTURE. Issue 1 (September 2020) - Natalya, Anisina; Anna, Bolshakova; Tatyana, Voloshinova; Elena, Ganapolskaya
Abstract: The article describes the longitude experiment on creating the communicatively orientated textbook on Russian speech culture. The problem of the majority of modern textbooks on speech culture is the lack of communication potential as they are usually based on texts from classical literature and that is why the language material is far from the professional needs of the university students (and especially the students of technical, mathematical and economical directions of education). The authors of the article conducted the linguistic researches in different language levels and proposed the principles of creating the textbook on speech culture with orientation on the professional needs of the university students. Then the principles were realized in the textbook "Russian Language and Speech Culture". The efficiency of the principles is affirmed during the experiment; students who studied the speech culture with the help of the textbook showed better results than the control groups. The textbook became one of the most popular manuals for practically orientated university students.